Association between periodontal health status and quality of life: a cross-sectional study - Al-Bitar, Kinan M.; Garcia, Jeffrey M.; Han, Shengtong; Guentsch, Arndt (Frontiers in Oral Health, 2024)
Introduction: Attachment loss due to periodontal diseases is associated with functional limitations as well as physical pain and psychological discomfort, which may lead to a reduced quality of life. The purpose of this study is to determine if the oral health status, specifically the periodontal status influences oral health related quality of life.Material and Methods: Survey data were collected in an U.S. dental school clinical setting in a crosssectional study. Quality of life related to oral health was assessed with the Oral Health Impact Profile (OHIP-49). Additionally, DMFT index, periodontal status, as well as health literacy scores (dental and medical health literacy) were recorded and the data of n=97 subjects was statistically analyzed.